Educação financeira para professores da rede pública de Rondônia: uma perspectiva da educação matemática crítica - Villar, Alexsander Fernandes (2025)
This dissertation presents the results of the design, implementation, and analysis of a course in financial education for public school teachers in the state of Rondônia, from the perspective of Critical Mathematics Education. The main objective was to analyze how a formative path, which articulates the teachers' experiences with practical tools and a critical approach, can develop pedagogical competencies for the integration of financial education into the school curriculum. The research, of an applied nature and mixed-method approach, integrated qualitative and quantitative procedures. Eight teachers from different fields took part in the study. The course was structured into four meetings, in which multiple data collection instruments were used, such as diagnostic questionnaires, the interactive Mentimeter platform, experience narratives, personal budget spreadsheets, discussion forums with case studies on the Moodle platform, and a final evaluation questionnaire. The data analysis, based on Content Analysis, revealed that the formative journey - starting from the reflection on the teachers' personal relationship with money, advancing to the instrumentalization on budgeting, credit, and debt, and culminating in the elaboration of pedagogical proposals - proved to be effective. The results indicate that the participants reframed their perceptions on the topic, appropriated financial management tools, and developed confidence to approach financial education in a critical and contextualized manner in the classroom, as validated by the positive evaluation of the intervention. The resulting educational product, in the format of a didactic sequence, which accompanies this study will be made available in the form of support material for basic education teachers on the program's website and on the EduCapes Portal at http://educapes.capes.gov.br/handle/capes/1174566.